DINAMIKA RESILIENSI MATEMATIS MAHASISWA DALAM PEMBELAJARAN GAMIFICATION (WORDWALL & QUIZIZZ): MENGUNGKAP SISI AFEKTIF DI BALIK SKOR DIGITAL - Ayu Silvi Lisvian Sari; Cicik Pramesti; Riki Suliana Ranggawati Sidik; Suryanti Suryanti (Universitas Tribhuwana Tunggadewi, 2025)
The integration of gamification platforms like Wordwall and Quizizz in higher education mathematics is often evaluated based on cognitive outcomes. However, the affective dimension, specifically mathematical resilience, remains under-explored. This qualitative research investigates the dynamics of students' mathematical resilience during gamified learning. The study involved 17 Mathematics Education students from Universitas PGRI Adi Buana PSDKU Blitar. Data were collected through participant observation, score documentation, and in-depth interviews. The thematic analysis revealed three main themes: (1)